Interactions between Transport Protein Particle (TRAPP) complexes and Rab GTPases in Arabidopsis. (5th August 2019) - Kalde, Monika; Elliott, Liam; Ravikumar, Raksha; Rybak, Katarzyna; Altmann, Melina; Klaeger, Susan; Wiese, Christian; Abele, Miriam; Al, Benjamin; Kalbfuß, Nils; Qi, Xingyun; Steiner, Alexander; et al.
Summary: Transport Protein Particle II (TRAPPII) is essential for exocytosis, endocytosis, protein sorting and cytokinesis. In spite of a considerable understanding of its biological role, little information is known about Arabidopsis TRAPPII complex topology and molecular function. In this study, independent proteomic approaches initiated with TRAPP components or Rab‐A GTPase variants converge on the TRAPPII complex. We show that the Arabidopsis genome encodes the full complement of 13 TRAPPC subunits, including four previously unidentified components. A dimerization model is proposed to account for binary interactions between TRAPPII subunits. Preferential binding to dominant negative (GDP‐bound) versus wild‐type or constitutively active (GTP‐bound) RAB‐A2a variants discriminates between TRAPPII and TRAPPIII subunits and shows that Arabidopsis complexes differ from yeast but resemble metazoan TRAPP complexes. Analyzes of Rab‐A mutant variants in trappii backgrounds provide genetic evidence that TRAPPII functions upstream of RAB‐A2a, allowing us to propose that TRAPPII is likely to behave as a guanine nucleotide exchange factor (GEF) for the RAB‐A2a GTPase. GEFs catalyze exchange of GDP for GTP; the GTP‐bound, activated, Rab then recruits a diverse local network of Rab effectors to specify membrane identity in subsequent vesicle fusion events. Understanding GEF−Rab interactions will be crucial to unravel the co‐ordination of plant membrane traffic. Significance Statement: The Arabidopsis proteome contains two distinct sets of TRAPP subunits, the first of which resembles metazoan TRAPPII, preferentially binds RAB‐A2a, and may act as a Guanosine Exchange Factor (GEF) for the TGN‐associated Rab‐A2 subclade of GTPases. The second set of TRAPP subunits resembles metazoan TRAPPIII and preferentially binds the vacuolar GTPase RAB‐G3f over RAB‐A2a, indicating that TRAPPIII may mediate degradative trafficking routes whilst TRAPPII mediates biosynthetic routes.